802.11 Wireless networks : - Gast, Matthew S. (O'Reilly, 2005)
802.11 Wireless networks: The definitive guide shows you how to configure wireless cards and Linux, Windows, and Mac OS X systems, and how to work with access points. Few books in any field combine the theory you need to know with the practical experience and advice you need to get things working.